Terahertz metamaterials with ultrahigh angular sensitivity - Born, Norman (2015)
A novel conceptual design methodology for strongly interacting metamaterials allows an ultrahigh angular sensitivity. Among others, this methodology enables precise sensing of the wave vector or the exclusion of unwanted directional radiation components. By diligently tailoring the dimensions of the primitive unit cell, an orders of magnitude enhanced sensitivity is achieved.